Company Responbility toward Employees Due to Pailit - Masitah Pohan (Budapest International Research and Critics University, 2021)
Company bankruptcy is a corporate legal phenomenon that is often greatly feared, either by company owners or by its management. Because with company bankruptcy, it means that the company has failed in doing business or at least has failed to pay its debts (debts). The purpose of this research is to identify and analyze the factors of company bankruptcy, the position of employees due to bankruptcy based on Law Number 13 of 2003, due to the legal consequences of bankruptcy against employees based on Law Number 37 of 2004. The research conducted is juridical normative, data sources which is used to support this research is a secondary data source. Factors for the occurrence of company bankruptcy are caused by unpredictable external factors, such as natural disasters. The position of employees due to bankruptcy based on Law Number 13 of 2003 is in Article 95 paragraph (4), clearly and emphasizes that wages and other rights of workers / labor are debts whose payment is prioritized to protect and ensure the survival of their lives and their families. . However, in reality the workers' position is under bankruptcy fees and curator fees, which means that workers must be more patient and stay behind after the bankruptcy of the bankruptcy estate is used to pay taxes, creditors who hold collateral (separatist creditors), bankruptcy fees and curator fees. The legal consequence of the occurrence of bankruptcy for employees based on Law Number 37 Year 2004 is Article 39 paragraph (1) of the Bankruptcy Law.